(untitled) (Materiali di Estetica. Terza serie, 2020)
Our aesthetic experience in Sobre los ángeles by Rafael Alberti observes the hard beat and various tensions contained in this collection of poems. They are those same tensions that sustain its poetic meaning, which is based on the organization of language and on the writing itself. The text is about a journey from heaven to hell, where a dark rhythm unveils the poet´s struggle to defeat the forces that threatened to destroy him. In our opinion, the analogy between the meaning of the poems and the rhythmic perceptions is noteworthy, what becomes a hollow rhythm that reflects the personal crisis of the poet. Although the tension has not been entirely resolved at the end, our reading underlines the success of an author who has achieved a unique tone that winds through the inner of each poem and involves the genesis of the whole.